OPERATIONS FOR BENIGN TUMORS OF THE AURICLE. CLINICAL CASE - Lutfullaev Gairat Umrullaevich; Safarova Nasiba Iskandarovna; Isaeva Zarinakhon Abdullaevna; Khalilov Muhriddin Oripovich (Western European Studies, 2024)
Surgical intervention for benign tumors has been and remains the main and almost the only method of treatment. Radiation treatment for these tumors is used extremely rarely. This is more often the exception than the rule
Keywords: benign tumors; surgery; external ear tumor